'Getting back to normal' or 'a new type of normal'? A qualitative study of patients' responses to the existential threat of cancer. (19th December 2014) - Baker, P.; Beesley, H.; Fletcher, I.; Ablett, J.; Holcombe, C.; Salmon, P.
Abstract : Existential concerns about cancer have been studied extensively in palliative care but less so in curative settings. The present report aims to describe ways in which patients viewed the continuity or discontinuity of their identity in the face of the mortal threat of cancer. Twenty‐eight patients with breast, prostate or lung cancer attending pre‐treatment, treatment or follow‐up appointments were interviewed about their emotional experiences following diagnosis. Qualitative analysis followed an inductive, constant comparative approach. Patients spoke of 'getting back to normal', but presented two distinct accounts of 'normality'. Some, particularly those only recently diagnosed, maintained continuity to past identity by upholding previous routines, emphasising resilience and minimising the impact of cancer. Others talked of a new 'normality' discontinuous with their past. Most accounts, however, evidenced elements of continuity and discontinuity, often in ostensibly contradictory ways. We suggest that holding contradictory perspectives simultaneously characterises an intermediate stage of adjustment for some patients: between reliance on continuity with the past in the aftermath of diagnosis and, later, a sense of being a new person, changed by cancer. Practitioners should appreciate that patients' wishes for 'normality' can signify very different responses to cancer, and that holding such contradictory orientations is functional, not aberrant.